AI-Based Training: ‘Speaking with Stimuler’ Program at SMAN 11 Garut - Nugraha, Irsyad; Fifian, Fifian; Ghandy, Ghandy; Hilda, Hilda; Dya, Dya; Hemalia, Hemalia; Nurjamin, Lucky Rahayu; Suparman, Asep; Fajriah, Yustika Nur (Fakultas Kewirausahaan Universitas Garut, 2025)
This community service program was carried out at SMAN 11 Garut with the aim of enhancing students’ speaking skills through the application of Artificial Intelligence (AI) using the “Speaking with Stimuler” approach. The activity was conducted in two stages, namely the delivery of materials by the service team and a hands-on practice session facilitated by the students. The results show that the integration of AI in speaking practice contributes to improving students’ language abilities, fostering more interactive learning experiences, and reducing repetitive burdens in the teaching process. Despite several challenges such as the need for continuous training and readiness of supporting infrastructure, the program proved effective in increasing students’ enthusiasm and competence. This activity highlights the potential of AI-based learning models as an innovative method to strengthen speaking skills in the context of secondary education. Keywords: Artificial Intelligence1; Speaking with Stimuler2; language learning3; community service4